1999
DOI: 10.1590/s0036-46651999000500002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory findings of disseminated Mycobacterium avium complex infection (DMAC) in a pair matched case-control study

Abstract: in order to define clinical and laboratory findings associated with DMAC infection in AIDS patients. Since DMAC infection is usually associated with advanced immunodeficiency, and therefore also with other opportunistic illnesses, in addition to the number of CD4 + lymphocytes, cases and controls were matched using the following criteria: date of AIDS diagnosis and antiretroviral therapy, number and severity of associated opportunistic infections and, whenever possible, type of Pneumocystis carinii prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…Haemoglobin levels were lower in the NTM disease group, probably indicating a chronic inflammatory anaemia or an NTM infection of the bone marrow (three patients had a positive culture from bone marrow). In case-control studies from the pre-HAART era, higher levels of gamma glutamyl transferase were found in patients with MAC infection suggesting a liver infiltration, 4,5 but in our study differences were not significant. A protracted clinical course with weight loss and symptoms for more than a month are useful indicators of an NTM infection if other diseases are excluded.…”
Section: Discussioncontrasting
confidence: 90%
“…Haemoglobin levels were lower in the NTM disease group, probably indicating a chronic inflammatory anaemia or an NTM infection of the bone marrow (three patients had a positive culture from bone marrow). In case-control studies from the pre-HAART era, higher levels of gamma glutamyl transferase were found in patients with MAC infection suggesting a liver infiltration, 4,5 but in our study differences were not significant. A protracted clinical course with weight loss and symptoms for more than a month are useful indicators of an NTM infection if other diseases are excluded.…”
Section: Discussioncontrasting
confidence: 90%